Direct Integration of Red‐NIR Emissive Ceramic‐like AnM6Xi8Xa6 Metal Cluster Salts in Organic Copolymers Using Supramolecular Interactions. Issue 19 (13th March 2018) - Robin, Malo; Dumait, Noée; Amela‐Cortes, Maria; Roiland, Claire; Harnois, Maxime; Jacques, Emmanuel; Folliot, Hervé; Molard, Yann
Abstract: Hybrid nanomaterials made of inorganic nanocomponents dispersed in an organic host raise an increasing interest as low‐cost solution‐processable functional materials. However, preventing phase segregation while allowing a high inorganic doping content remains a major challenge, and usual methods require a functionalization step prior integration. Herein, we report a new approach to design such nanocomposite in which ceramic‐like metallic nanocluster compounds are embedded at 10 wt % in organic copolymers, without any functionalization. Dispersion homogeneity and stability are ensured by weak interactions occurring between the copolymer lateral chains and the nanocluster compound. Hybrids could be ink‐jet printed and casted on a blue LED. This proof‐of‐concept device emits in the red‐NIR area and generates singlet oxygen, O2 ( 1 Δg), of particular interest for lights, display, sensors or photodynamic based therapy applications. Abstract : Blue Light, Red Light : High contents of phosphorescent octahedral metal clusters are homogeneously integrated within in an acrylate matrix using supramolecular interactions. The resulting hybrid materials can be processed by inkjet printing and, once deposited on a blue LED, generate bright‐red‐NIR light and singlet oxygen.